2017
DOI: 10.3390/rs9040318
|View full text |Cite
|
Sign up to set email alerts
|

Toward Generic Models for Green LAI Estimation in Maize and Soybean: Satellite Observations

Abstract: Abstract:Informative spectral bands for green leaf area index (LAI) estimation in two crops were identified and generic models for soybean and maize were developed and validated using spectral data taken at close range. The objective of this paper was to test developed models using Aqua and Terra MODIS, Landsat TM and ETM+, ENVISAT MERIS surface reflectance products, and simulated data of the recently-launched Sentinel 2 MSI and Sentinel 3 OLCI. Special emphasis was placed on testing generic models which requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…These results suggest a need for testing new vegetation indices adopting L8 bands. In agreement with our results, other studies comparing linear additive models showed a similar ability in estimating canopy cover and LAI adopting the S2 or L8 sensors (Korhonen et al, 2017).…”
Section: Satellite Sensors As Estimators Of Gppsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest a need for testing new vegetation indices adopting L8 bands. In agreement with our results, other studies comparing linear additive models showed a similar ability in estimating canopy cover and LAI adopting the S2 or L8 sensors (Korhonen et al, 2017).…”
Section: Satellite Sensors As Estimators Of Gppsupporting
confidence: 93%
“…The red edge corresponds to the steep increase in reflectance at the boundary between the red region, where chlorophyll is absorbed, and the leaf scattering at the NIR region. Red-edge bands were successfully employed to estimate chlorophyll content in maize (Zhang and Zhou, 2017) and LAI in crops (Kira et al, 2017). For these reasons they were integrated into numerous VIs, such as MTCI and PSRI, which were also applied in this study.…”
Section: Are Spectral Bands Better Gpp Estimators Than Vis?mentioning
confidence: 99%
“…We propose that two processes are having an effect here: first, as the canopy becomes optically thicker, underestimation of LAI is expected [17], and secondly, the comparison of coarse resolution observations with point measurements introduces the effects of sub-pixel landscape heterogeneity [75,76]. In the literature [77,78], the use of empirical methods that have been trained with ground observations of the same area limits the generality of the methods for global applications. Additionally, no simultaneous inferences on FAPAR are presented in either of these two references.…”
Section: Discussionmentioning
confidence: 99%
“…The use of too many bands may also cause over‐fitting of the model to the trained data. Several studies have demonstrated that estimation accuracy was higher when using several defined spectral bands than when using the full spectral information available from a sensor (Meroni et al, 2004; Darvishzadeh et al, 2008; Verrelst et al, 2013, 2016; Kira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The data processing was performed similarly to previously published papers estimating green LAI in these crops (Kira et al, 2016, 2017). Training and validation processes included the testing of all possible combinations of spectral bands and a 10‐fold cross validation.…”
Section: Methodsmentioning
confidence: 99%